Challenges and Opportunities for Ecotourism Development: A Study in the Post-war Context in the Northern Province of Sri Lanka: Cabaran dan Peluang kepada Pembangunan Eko-Pelancongan: Satu Kajian dalam Konteks Pasca- Perang di Wilayah Utara Sri Lanka - Gunawardana, Shashi Madhushanka; Aloysius, Nitharsan; Chandrika, Chathuri (GEOGRAFI, 2022)
Following several decades of political unrest, the northern province was finally opened for visitors. There are hundreds of novel opportunities available for ecotourists that they may have never experienced before. Nevertheless, the northern province had not achieved its optimum level in terms of ecotourism due to several reasons. A one-year study from January to December 2020 was conducted to investigate the available opportunities, resources, and challenges. Primary data were collected through an online questionnaire survey and occasional visits to the area and secondary data were gathered from the internet, published research articles, scientific reports, provincial council reports, and data from government institutes. Qualitative descriptive statistics were used to analyze the data. The majority (72%) answered that there is a great potential to develop the province as an ecotourism destination. However, the majority replied that several challenges exist including lack of infrastructure, lack of institutional and community participation, lack of transportation facilities, less popularity, lack of accessibility, and lack of awareness. According to the secondary data, there are numerous opportunities and resources available for ecotourism including wildlife areas, forest reserves, cultural places, traditional dancing, and foods. Hence, proper planning involving all the stakeholders should be implemented to overcome challenges and promote the northern province as an important ecotourism destination in Sri Lanka.